Step-by-step explanation:
Start by finding (fog)(x)
To find this function, substitute x=
x−1
4
That is g(x) into f(x)
⇒(f∘g)(x)=(
x−1
4
)
2
−2(
x−1
4
)+5
=
(x−1)
2
16
−
x−1
8
+5
Now substitute x=3
⇒(f∘g)(3)=
(3−1)
2
16
−
3−1
8
+5
=
4
16
−
2
8
+5=4−4+5=5.
Hope it helps:)
Answer:
8
Step-by-step explanation:
Hope it helps
:D
Can i have brainly pls
Given:
3, -2
1, 2
-1, -4
-1, 2
The format is (x,y)
The domain is all the x-values while range is all the y-values.
domain: (3,1, -1,-1) 2nd option given.
I am also not able to solve thi s question